STUDI MUKA AIR TANAH GAMBUT DAN IMPLIKASINYA TERHADAP DEGRADASI LAHAN PADA BEBERAPA KUBAH GAMBUT DI KABUPATEN SIAK - Soewandita, Hasmana (Jurnal Air Indonesia, 2008)
Overdrainaged phenomena on peat land after reclamated for agriculture area is indicated water management/water table control failure. Water table depth of peat land on virgin forest that has been reclamated is low (0.15 m) and this condition on Zamrud peat dome. Water table dept on old reclamated peat land has better condition than peat land after new reclamated as plantation area. Peatland degradation showed overdrainage phenomena has potential happened on land clearing and canal construction activity. This condition have effected to water table dept about 1 m. Overdrainaged impact on peatland has caused fire of peatland. For example this condition occured in Siak Kecil peat dome and Kandis peat dome. Keywords : peat dome, water table